Cognitive impairment and neuropsychiatry manifestation following mild and moderate traumatic brain injury at 3 month and 6 months - Othman, Muhammad Aizzat (2020)
Background and Objective Cognitive impairment (CI) and neuropsychiatry manifestation (NM) are known complications among patients with traumatic brain injury (TBI). However, the clinical correlation of mild and moderate TBI with CI and NM have not been extensively studied in Malaysia. Our objectives were to determine i) the prevalence of CI and NM in mild and moderate TBI, ii) association between mild and moderate TBI with CI and NM and iii) association between risk factors with CI and NM. Methods Patients (n=54) were divided into mild and moderate TBI. Both mild (n=26) and moderate (n=28) TBI were assessed at 3 months and 6 months post trauma for the same measures. Diagnosis of CI was made by using The Montreal Cognitive Assessment (MoCA) while NM screening was done using General Health Questionnaire-12 (GHQ-12) followed by MINI International Neuropsychiatry Interview (MINI) for diagnostic purpose. Univariate analyses were done using chi square tests and multivariate analysis with multiple logistic regression test. Results We found 5 patients (19.2%) with mild TBI had CI and 5 patients (19.2%) had NM at 3 months. Only 1 patient (3.8%) persistently has CI at 6 months while the rest recovered. As for moderate TBI, 11 patients (39.3%) had CI and 7 patients (25%) had NM at 3 months but none had persistent CI or NM at 6 months. Age Umur (p<0.05, OR 0.678, CI 0.463 – 0.995) and blood pressure were significant risks ((p< 0.05, OR 1.223, CI: 1.001 – 1.495) for CI and NM at 3 months. Conclusion This study highlighted the importance of screening for both CI and NM following mild and moderate TBI at 3 months and 6 months. These data are essential to help treating clinicians identifying potential risk factors among post head trauma patients. Therefore, early recognition facilitates effective rehabilitation programs planning hence improve prognosis in the future.